Antitumor effect of the Newcastle disease viral hemagglutinin–neuraminidase gene is expressed through an oncolytic adenovirus effect in osteosarcoma cells. Issue 3 (March 2018) - Chen, Shuang; Zhang, Qinggao; Xu, Duo; Li, Yiquan; Fan, Yuanyuan; Li, Wenjie; Yin, Xunzhe; Zhang, Yang; Liu, Jingwei; Li, Xiao; Sun, Lili; Jin, Ningyi
Abstract : Newcastle disease virus (NDV) can specifically kill cancer cells and has less toxicity to normal cells. The hemagglutinin–neuraminidase (HN) protein is an important structural protein in NDV pathogenesis and has been postulated as a promising candidate for antitumor therapy. The aim of this study was to investigate the anticancer potential of recombinant adenovirus Ad-HN-PEG3p-E1a. An MTS assay was performed to determine viral proliferation after viral infection, the data showed that the proliferation ability of osteosarcoma cells decreased, whereas there was no significant change in normal hepatic cells. DAPI and Annexin V experiments showed that osteosarcoma cells were killed because of apoptosis, active oxygen content, and augmented mitochondrial membrane potential loss. Caspase Activity Assay Kits were used to detect the caspase-3 activities of the treated OS-732 for increased expression. Western blot analysis showed that cytochrome C increased significantly and apoptosis of the virus was confirmed in tumor cells. In-vivo experiments show that NDV has an inhibitory effect on tumor growth. The recombinant adenovirus, which is composed of a HN protein and progressive increment promoter PEG3p, could inhibit the growth of OS-732 and promote the apoptosis of tumor cells. However, there was no clear relationship with normal cell (L02) apoptosis.